Studies on Eco-friendly stickers - Krishna, R.Hema (International Journal of Engineering and Technology, 2024)
Beyond expediting the checkout process, the labels carry significant information about the fruit’s journey from farm to table. While applicable to vegetables, herbs, and nuts as well, fruits predominantly bear these labels, offering valuable insights into their cultivation methods. Each sticker contains the PLU (Price Look-Up) number, but that’s not all. Produce stickers are full of information about the fruit and veggies you purchase at the supermarket. The objective of this paper is to provide a comprehensive overview of the existing situation and to study the Eco-friendly labeling of fresh fruits and vegetables.